Chloroplast Protein 12 Expression Alters Growth and Chilling Tolerance in Tropical Forage Stylosanthes guianensis (Aublet) Sw - Li, Kailong; Qiu, Hong; Zhou, Min; Lin, Yang; Guo, Zhenfei; Lu, Shaoyun (Frontiers in Plant Science, 2018)
Stylosanthes guianensis (Aublet) Sw. is a tropical forage legume with soil acidity tolerance and excellent adaptation to infertile soils, but sensitive to chilling. To understand the molecular responses of S. guianensis to chilling, differentially expressed genes between a chilling tolerant mutant 7-1 and the wild type were identified using suppression subtractive hybridization, and eight of them were confirmed and the regulation pattern were analyzed using quantitative reverse transcription PCR (qRT-PCR). Chloroplast protein 12 (CP12) functions to regulate the Calvin cycle by forming a ternary complex with glyceraldehyde 3-phosphate dehydrogenase (GAPDH) and phosphoribulokinase (PRK). SgCP12 transcript was induced by chilling in both plants, and higher levels were observed in 7-1 than in the wild type, implying a potential role of SgCP12 in chilling tolerance. To confirm this, transgenic S. guianensis plants over-expressing or down-regulating SgCP12 were generated respectively. Higher Fv/Fm and survival rate and lower ion leakage were observed in transgenic plants overexpressing SgCP12 as compared with the wild type after chilling treatment, while lower Fv/Fm and survival rate and higher ion leakage were found in SgCP12 antisense plants. SgCP12 overexpression plants showed promoted growth with increased plant height and fresh weight, while the antisense plants exhibited reduced growth with decreased plant height and fresh weight as compared with the wild type. The results indicated that regulation of SgCP12 expression alters plant growth and chilling tolerance in S. guianensis. In addition, higher levels of net photosynthetic rate (Pn), GAPDH and PRK activities were observed in SgCP12 overexpression transgenic plants, while lower levels in antisense plants than in the wild type under both control and chilling conditions, indicating that altered activities of GAPDH and PRK were associated with the changed Pn in transgenic S. guianensis. Our results suggest that SgCP12 regulates GAPDH and PRK activities, Pn, and chilling tolerance in S. guianensis.